2017
DOI: 10.5194/acp-17-13119-2017
|View full text |Cite
|
Sign up to set email alerts
|

Frequent ultrafine particle formation and growth in Canadian Arctic marine and coastal environments

Abstract: Abstract. The source strength and capability of aerosol particles in the Arctic to act as cloud condensation nuclei have important implications for understanding the indirect aerosolcloud effect within the polar climate system. It has been shown in several Arctic regions that ultrafine particle (UFP) formation and growth is a key contributor to aerosol number concentrations during the summer. This study uses aerosol number size distribution measurements from shipboard expeditions aboard the research icebreaker… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 110 publications
16
71
0
Order By: Relevance
“…The values of trueδP̿ and trueδP¯ were nearly zero below an altitude of 4 km, especially during the summer months; trueδP̿ had minimum values in July and August (Figure b), corresponding to the largest lidar‐observed trueβM532̿ values (Figure a). Observations in the Arctic boundary layer have shown active particle formation during the summer (Collins et al, ; Freud et al, ; Tunved et al, ). At higher altitudes, Scheuer et al () reported a sharp increase in the mixing ratio of sulfate ions in free tropospheric fine aerosol particles over the Arctic during March.…”
Section: Discussionmentioning
confidence: 99%
“…The values of trueδP̿ and trueδP¯ were nearly zero below an altitude of 4 km, especially during the summer months; trueδP̿ had minimum values in July and August (Figure b), corresponding to the largest lidar‐observed trueβM532̿ values (Figure a). Observations in the Arctic boundary layer have shown active particle formation during the summer (Collins et al, ; Freud et al, ; Tunved et al, ). At higher altitudes, Scheuer et al () reported a sharp increase in the mixing ratio of sulfate ions in free tropospheric fine aerosol particles over the Arctic during March.…”
Section: Discussionmentioning
confidence: 99%
“…Some observations in productive marine areas of the Canadian Arctic Archipelago have indicated higher growth rates (Burkart, Hodshire, et al, ; Collins et al, ). Two years of ship‐based observations indicated a mean apparent growth rate of 4.3 ± 4.1 nm/hr, with some events of ≥10 nm/hr (Collins et al, ). The impact of Arctic anthropogenic emissions from petroleum extraction has been shown to influence particle growth rates; at Utqiaġvik air masses from Prudhoe Bay showed a higher mean growth rate (2.7 ± 2.5 nm/hr) and more frequent particle formation compared to clean marine air masses (1.8 ± 1.5 nm/hr; Kolesar et al, ).…”
Section: Regional Arctic Processesmentioning
confidence: 99%
“…Melt pond water temperatures and salinities varied between 0.21 and 1.86 • C and between 0.2 and 8.5, respectively. Chl a concentrations were (Cox and Weeks, 1983;Petrich and Eicken, 2010).…”
Section: Physical Chemical and Biological Characteristics Of The Mementioning
confidence: 99%
“…Clean Arctic air masses allow ultrafine (5-20 nm diameter) particle formation and the potential growth of secondary marine organic aerosols (including DMS-derived particles) into CCN (Willis et al, 2016). Hence, the Arctic is a favourable terrain for new particle formation from biogenic DMS Rempillo et al, 2011;Collins et al, 2017;Giamarelou et al, 2016;Mungall et al, 2016;Willis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%